ENVIRONMENTAL IMPACT OF WATER TREATMENT PROCESS. A SYSTEMATIC REVIEW OF EVALUATION METHOD - FLORINA FABIAN; VALENTIN NEDEFF; MIRELA PANAINTE -LEHADUS; OANA IRIMIA; SILVIA RACOVITA (Journal of Engineering Studies and Research)
In an international context in continuous development, water treatment processes become an important component of society where we live. Attention is directed on water treatment processes in the context of increasing water demand. This study proposes a systematic review of methods for the assessment of the environmental impact of Water Treatment process. The approach is based on the evaluation of LCA, Externalities Evaluation methodology and Carbon Footprint methodology, each of these methods have the environmental indicators able to relate direct and indirect emissions generated by any water treatment process. The present review compares and discusses the implementation of the above-cited methodologies to different case studies. The results in short show that Carbon Footprint only assesses the global warming potential of a water treatment plant, whereas Life Cycle Analysis and assess multiple environmental impact categories, which may include global warming, but also impacts on human health, ecosystems quality, etc. There are different standards and organizations around each assessment. The ExternE method on the contrary aims to quantify external impacts, from both economic and social points of view, to weight each endpoint of the impact categories.